2006
DOI: 10.1007/s11211-006-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

On Gratitude

Abstract: In this review, I use Emmons and McCullough's excellent volume on gratitude as a platform for discussing several issues in emotion,cultural, and moral psychology. First I summarize this exceptionally rich edited book, which provides accessible reviews of the philosophy,theology, anthropology, sociology, evolutionary biology, and psychology of gratitude. I next take up four questions inspired by the book. First, I consider whether gratitude is an emotion, and how to operationally define emotions. Second, I disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
1
20
0
2
Order By: Relevance
“…This is consistent with findings that gratitude may predict a greater life span (Danner et al, 2001). The sense of appreciation from experiencing gratitude is believed to make the heart rhythm smooth and harmonious, enhancing coherence within the body and increasing physical health and wellbeing (Cohen, 2006).…”
Section: Benefits Of Gratitudesupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with findings that gratitude may predict a greater life span (Danner et al, 2001). The sense of appreciation from experiencing gratitude is believed to make the heart rhythm smooth and harmonious, enhancing coherence within the body and increasing physical health and wellbeing (Cohen, 2006).…”
Section: Benefits Of Gratitudesupporting
confidence: 88%
“…Fredrickson (2004) found that individuals who experienced positive emotions had the ability to explore their environment, obtaining vital survival resources. The broaden-and-build model may also encourage individuals to become more creative in their methods of reciprocating and reflecting gratitude (Cohen, 2006). In addition, a positive emotion such as gratitude is believed to improve broad-minded coping, which has been shown to increase positive affect (Fredrickson and Joiner, 2002).…”
Section: Broaden-and-build Theorymentioning
confidence: 99%
“…Javaslata szerint az elkülönítés alapja az lehet, hogy a hála per definitionem magában foglalja az ágensre vonatkozó attribúciókat. Így a Grand Canyon látványa válthat ki áhítatot, egy lottónyeremény öröm-mámort, de hálát nem (Cohen, 2006).…”
Section: A Hála Konceptualizálásaunclassified
“…It also raises the question of whether the beneficiary feels as grateful to those of higher status from whom benefits are expected. Appadurai also indicates that Tamil gratitude focuses more on the benefits of benefaction than on the benefactor (see also Cohen, 2006) -which might suggest a different relationship between beneficiary and benefactor than is common in Western cultures.…”
mentioning
confidence: 99%